2016
DOI: 10.4236/jamp.2016.48174
|View full text |Cite
|
Sign up to set email alerts
|

Bending and Vibrations of a Thick Plate with Consideration of Bimoments

Abstract: The paper is dedicated to the development of the theory of orthotropic thick plates with consideration of internal forces, moments and bimoments. The equations of motion of a plate are described by two systems of six equations. New equations of motion of the plate and the boundary conditions relative to displacements, forces, moments, and bimoments are given. As an example, the problems of free and forced oscillations of a thick plate are considered under the effect of sinusoidal periodic load. The problem is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It should be noted that the equations of motion for the bimoment theory of plates of constant thickness developed in [13] [14] [15] [16] could be obtained from the constructed systems of equations. It could be shown that to obtain numerical results with satisfactory accuracy, it is sufficient to take into account eight terms of the series (4).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the equations of motion for the bimoment theory of plates of constant thickness developed in [13] [14] [15] [16] could be obtained from the constructed systems of equations. It could be shown that to obtain numerical results with satisfactory accuracy, it is sufficient to take into account eight terms of the series (4).…”
Section: Resultsmentioning
confidence: 99%
“…Thus causing a decrease in the value of thermal conductivity [13,14]. We note in Fig.5 The thermal conductivity starts to decrease with increasing immersion time this is because the process of immersion in chemical acid may cause, break down the chemical bonds and slip because this acid solution attacks the polymer strongly due to positive ions (H +) works to form a bond With the ends of the polymer chains and negative ions (SO 4 -) attack and weakness the interstitial area and therefore this acid has caused a disruption of the transfer of the phonons, which are responsible for the transfer of heat [15,16]. Table 3 shows the practical results of the Impact strength values for samples reinforced by silicon dioxide before and after immersion in sulfuric acid.…”
Section: Second: Preparation Of Thermal Conductivity Test Modelsmentioning
confidence: 99%
“…This article proposes a method for calculating the structures for seismic resistance on the basis of a continuum plate model developed in the framework of the bimoment theory [8][9][10][11][12][13][14][15][16][17], taking into account the spatial stress-strain state. If to consider the law of nonlinearity of displacements distribution in the cross-sections of the plate, then in addition to tensile and shear forces, bending and torsional moments, there appear the additional force factors, called the bimoments.…”
Section: Introductionmentioning
confidence: 99%